Role of silica nanoparticles in pathogenesis of Mesoamerican nephropathy - Addanki, Raja Narendra Divakar; Mannava, Anjali Srikanth (International Journal of Research in Medical Sciences, 2023)
The authors have done an excellent job in shedding light on Mesoamerican nephropathy (MeN), a lesser-known variant of chronic kidney disease that affects agricultural workers in rural areas especially regions with hot climates like Central America, etc. The inclusion of social factors in the pathogenesis and highlighting the risks posed by nephrotoxic drugs and heat stress leading to subclinical rhabdomyolysis and uricosuria are crucial contributions to the understanding of MeN.